2021
DOI: 10.1016/j.bioactmat.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Marginal sealing around integral bilayer scaffolds for repairing osteochondral defects based on photocurable silk hydrogels

Abstract: Osteochondral repair remains a major challenge in current clinical practice despite significant advances in tissue engineering. In particular, the lateral integration of neocartilage into surrounding native cartilage is a difficult and inadequately addressed problem that determines the success of tissue repair. Here, a novel design of an integral bilayer scaffold combined with a photocurable silk sealant for osteochondral repair is reported. First, we fabricated a bilayer silk scaffold with a cartilage layer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 52 publications
0
65
0
Order By: Relevance
“…[ 54 ] As a result, the more calcified tissue and mature bone formation were found in the implanted area than the control groups without growth factors; however, empty fissures were observed in the cartilage area and connective tissues were also found in the subchondral bone area. [ 54 ] The deficient regeneration might be caused by the off‐targeted and inconsistent delivery of growth factors. [ 55 ] Unlike these approaches, the biphasic construct developed in our approach contained the composite spheroids (BS and TS), which have specifically given the inductive signals to stem cells in a stable manner with reduced amount of BMP‐2 (totally 1.8 µg) or TGF‐ β 3 (totally 0.9 µg) from the inside of a spheroid, showed the more effective differentiation of stem cells (Figure 3 ), continuously reproduced the growth factors (Figure S4 , Supporting Information), and finally succeeded in volumetric regeneration of critical sized osteochondral defect (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 54 ] As a result, the more calcified tissue and mature bone formation were found in the implanted area than the control groups without growth factors; however, empty fissures were observed in the cartilage area and connective tissues were also found in the subchondral bone area. [ 54 ] The deficient regeneration might be caused by the off‐targeted and inconsistent delivery of growth factors. [ 55 ] Unlike these approaches, the biphasic construct developed in our approach contained the composite spheroids (BS and TS), which have specifically given the inductive signals to stem cells in a stable manner with reduced amount of BMP‐2 (totally 1.8 µg) or TGF‐ β 3 (totally 0.9 µg) from the inside of a spheroid, showed the more effective differentiation of stem cells (Figure 3 ), continuously reproduced the growth factors (Figure S4 , Supporting Information), and finally succeeded in volumetric regeneration of critical sized osteochondral defect (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 80 ] To solve this limitation, MSC spheroids were pre‐positioned within carriers such as alginate/hyaluronic hydrogel, decellularized matrix, and 3D‐printed PCL scaffold before transplantation. [ 53 , 54 ] However, the regeneration was not improved dramatically because the spheroids could not be differentiated specifically into cartilage or bone without induction of osteogenic or chondrogenic growth factors. [ 83 ] In our previous study, we demonstrated that both instructive growth factors and carriers for spheroids were necessary for formation of mature bone in a mouse calvarial bone defect.…”
Section: Discussionmentioning
confidence: 99%
“…created a photocurable methacrylate silk fibroin to seal the gap between the bi-layered silk scaffold and adjacent cartilage. Under the high bioactivity of this sealing hydrogel, native BM-MSCs migrated to scaffold-native tissue interface to promote cartilage regeneration [ 64 ]. Recently, several bi-layered scaffolds, including Agili-C™, BioMatrix CRD®, TruFit® Plug, OsseoFit® Plug, and so forth, for the osteochondral defect treatment have been on the stage for clinical trials or approved for clinical application [ 46 ].…”
Section: Articular Cartilage Regeneration Under Abnormal Conditionsmentioning
confidence: 99%
“…Crystals are removed subsequently The electrohydrodynamic technique, also known as rapid prototyping or solid freeform fabrication, is classified into seven processes: vat photopolymerization, material jetting, material extrusion, powder bed fusion, directed energy deposition, sheet lamination and binder jetting. Tang et al (2016); Gibbs et al (2014) technology (Wu et al, 2021). The lyophilized silk powder was first mixed with hexafluoroisopropanol (HFIP) solution with or without sucrose particles in a silicone mold.…”
Section: ) Microfluidic Foamingmentioning
confidence: 99%
“…The chitosan/alginate gel was treated through a series of steps for scaffold fabrication such as lyophilization, cross-linking and elution. Wu et al evaluated the efficacy of bilayered silk scaffolds loaded with TGF-β3/BMP-2 for osteochondral defect repair in rabbits aided by the solvent casting/particulate leaching technology ( Wu et al, 2021 ). The lyophilized silk powder was first mixed with hexafluoroisopropanol (HFIP) solution with or without sucrose particles in a silicone mold.…”
Section: Scaffold Fabrication Techniquesmentioning
confidence: 99%